Characteristics and influencing factors of neuroendocrine dysfunction in patients with adult-onset craniopharyngioma - Guo, Ying; Gui, Songbai; Liu, Pinan; Zhang, Yazhuo; Zhong, Liyong; Xu, Jian (Frontiers in Endocrinology, 2025)
ObjectiveThe aim of the study was to compare neuroendocrine dysfunction patterns in adult-onset adamantinomatous craniopharyngiomas (ACPs) and papillary craniopharyngiomas (PCPs) before and after surgery, and identify factors that influence neuroendocrine outcomes in these two histopathological types.MethodsA retrospective analysis was conducted on 390 patients with adult-onset craniopharyngioma (CP) patients, including 272 patients with ACP and 118 patients with PCP. The pre- and post-operative neuroendocrine parameters were compared, and the factors that contributed to poor endocrine outcomes were identified.ResultsSuprasellar tumor extension (83.1% vs. 70.6%, p = 0.01), mass effects (81.4% vs. 68.4%, p<0.01), and pre-operative central diabetes insipidus (CDI; 35.6% vs. 21.0%, p = 0.02) rates were higher in the PCP group, when compared to the ACP group. However, both PCP and ACP patients presented with a post-operative increase in growth hormone deficiency (GHD), CDI, and hypothalamic-pituitary-target dysfunction (p<0.05 vs. pre-operative baselines). Furthermore, the hypothalamic-pituitary-adrenal (HPA) axis dysfunction (75.4% vs. 65.3%, p = 0.04) and GHD (50.0% vs. 34.7%, p<0.01) rates were higher in the ACP group, when compared to the PCP group. Surgical intervention had a greater detrimental effect on overall pituitary function in ACP patients, when compared to PCP patients. The ACP pathological type, larger tumors, and milder pre-operative endocrine dysfunction were associated with a significantly higher risk of postoperative pituitary hormone deficiencies (p<0.05).ConclusionsSurgical intervention may exacerbate pituitary dysfunction in adult patients with ACP and PCP, although different factors influence the adverse endocrine outcomes for these two pathological types.